2019
DOI: 10.1590/1414-462x201900020068
|View full text |Cite
|
Sign up to set email alerts
|

Desafios e estratégias para doação de sangue e autossuficiência sob perspectivas regionais da Espanha e do Brasil

Abstract: Resumo Introdução O sangue, seus componentes e derivados são imprescindíveis para o funcionamento da atenção hematológica e transfusional nos sistemas de saúde modernos. Objetivo Identificar algumas das dificuldades, dos desafios e das estratégias que os serviços de hemoterapia públicos experimentam no momento atual, a partir de perspectivas regionais na Espanha e no Brasil. Método Foram realizadas entrevistas com onze gestores/profissionais de serviços de hemoterapia das Comunidades Autônomas de Madri, Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
6
Order By: Relevance
“…This finding may indicate the need to direct efforts to raise awareness and motivate young people and women to become regular donors to ensure a constant blood supply over time. In this sense, for young people, social networks can be an option, as well as carrying out actions in educational contexts and receiving visits from groups of schoolchildren in hemotherapy services [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may indicate the need to direct efforts to raise awareness and motivate young people and women to become regular donors to ensure a constant blood supply over time. In this sense, for young people, social networks can be an option, as well as carrying out actions in educational contexts and receiving visits from groups of schoolchildren in hemotherapy services [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Jesus et al, 2021;Da Silva, 2021) Nesse sentido, a Organização Mundial da Saúde (OMS) afirma que os estabelecimentos voltados para a doação de sangue devem possuir serviços organizados e eficazes, seguindo o regulamento e disposições legislativas, além de garantir a segurança do receptor. (Souza & Santoro, 2019). De acordo com a resolução RDC -ANVISA nº 34 de 11 de junho de 2014 afirma que deve ser estabelecido requisitos de boas práticas para garantir qualidade dos processos e produtos, riscos sanitários e segurança transfusional.…”
Section: Introductionunclassified
“…Both in Brazil and in other countries, such as Spain, there are difficulties in maintaining sufficient blood supplies to meet the current transfusion demand. Through interviews with managers and professionals of hemotherapy services, the authors identified impasses related to attracting and retaining donors, as well as factors associated with infrastructure and resources (SOUZA; SANTORO, 2019).…”
Section: Introductionmentioning
confidence: 99%